The Influence of Principal Supervision on High School Teacher Performance - Gesti Meriani; Bambang Ismaya; Abduloh (South Sulawesi Education Development (SSED), 2025)
This study aims to analyze the influence of principal supervision on teacher performance at SMAN 1 Cikarang Pusat, Bekas Regency, West Java. In the VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) era, the world of education is facing rapid changes that require continuous adaptation to improve the quality of teachers as a key factor in achieving effective learning. However, preliminary studies show gaps in teacher performance, especially in learning planning, learning delivery, interpersonal relationships, and assessment methods. This study uses a quantitative approach with a correlational regression method to test the relationship between principal supervision and teacher performance. Data was collected through a questionnaire involving 63 teachers as respondents. The results showed that the supervision of the principal had a significant effect on teacher performance, with a positive correlation coefficient of 0.869 and an R-Square value of 55.8%, which showed that more than half of the variation in teacher performance could be explained by supervision. However, there are still gaps in implementation, especially in the implementation and follow-up of supervision. This research highlights the importance of a structured supervision program, continuous professional development, and active involvement of teachers in the supervision process. These findings contribute to the development of a more effective supervision model to improve teacher performance and ultimately improve the quality of education in Indonesia.